Analisis Pemahaman Bunga Bank Dan Sistem Bagi Hasil Di Pusat Pasar Kota Medan - Dimas Bayu (AGHNIYA : Jurnal Ekonomi Islam, 2020)
This study aims to see the understanding of the traders in the Medan City market center on bank interest and profit sharing systems. Many people still equate the interest system and profit sharing system, this is also the same as the understanding that exists in the traders. The method used in this study is descriptive qualitative method, data collection by distributing inventory to traders. Sampling by means of snowball sampling, if it feels the sample has not fulfilled, then add samples, until finally it is enough. The results obtained, that the traders understand about bank interest and profit sharing systems in financial institutions. These results are reinforced by the results of interviews conducted by traders, that traders do understand about the bank's interest system and the profit sharing system in financial institutions.